2017
DOI: 10.1186/s13256-017-1244-0
|View full text |Cite
|
Sign up to set email alerts
|

Two synchronous malignant tumors of the pancreas: a case report

Abstract: BackgroundOnly a limited number of multiple synchronous primary malignancies of the pancreas have been reported in the medical literature. We report a case of two solid malignant tumors of the pancreas diagnosed preoperatively.Case presentationWe describe a 65-year-old Sri Lankan woman who presented with progressive obstructive jaundice. Initial contrast-enhanced computed tomography imaging detected a malignant tumor at the tail of her pancreas. A second tumor of the pancreatic head was detected with integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Multiple primary cancers are considered when each tumor is definitively malignant and they are primary tumors located distant from each other (2). To our knowledge, only two cases of pancreatic adenocarcinoma and a synchronic ampullary adenocarcinoma have been reported so far (1,3). The present case would be the third since it meets the proposed criteria, as both tumors were adenocarcinomas, located in different areas and the molecular analysis excluded the possibility metastasis.…”
Section: Discussionmentioning
confidence: 57%
“…Multiple primary cancers are considered when each tumor is definitively malignant and they are primary tumors located distant from each other (2). To our knowledge, only two cases of pancreatic adenocarcinoma and a synchronic ampullary adenocarcinoma have been reported so far (1,3). The present case would be the third since it meets the proposed criteria, as both tumors were adenocarcinomas, located in different areas and the molecular analysis excluded the possibility metastasis.…”
Section: Discussionmentioning
confidence: 57%
“…Histological findings of multifocal adenocarcinoma usually reveals precancerous lesions (e.g., intraductal papillary mucinous neoplasms (IPMNs) [ 13 - 14 ] and pancreatic intraepithelial neoplasia (PanIN) [ 13 ]) giving chronic pancreatitis-like changes [ 13 - 14 ], but interestingly, in our two cases, there were no precancerous lesions identified. The pathogenesis of the multifocal pancreatic adenocarcinoma is still unknown.…”
Section: Discussionmentioning
confidence: 84%
“…In a study of pancreatic and periampullary collision cancers, 5 out of 10 cases were reported to have adenocarcinoma, only 2 of which were found within the pancreas . De Silva et al reported a case with an ampullary pancreatic‐type adenocarcinoma and a colloid‐type adenocarcinoma in the pancreatic tail . Cases of serous cystadenoma of the pancreas synchronous with adenocarcinoma have also been reported .…”
Section: Discussionmentioning
confidence: 99%
“…16 De Silva et al reported a case with an ampullary pancreatic-type adenocarcinoma and a colloid-type adenocarcinoma in the pancreatic tail. 23 Cases of serous cystadenoma of the pancreas synchronous with adenocarcinoma have also been reported. 21,24 Our case is among the few synchronous pancreatic tumors with adenocarcinoma and NET components.…”
Section: Discussionmentioning
confidence: 99%